Preparation and characterization of bioceramic nanocomposites based on hydroxyapatite (HA) and carboxymethyl cellulose (CMC) - Kumar, Annamalai Pratheep; Mohaideen, Kamal Khaja; Alariqi, Sameh A. S.; Singh, Raj Pal (Macromolecular Research, 2010)
We report the synthesis of biomimetic nanocomposites based on carboxymethyl cellulose (CMC) and hydroxyapatite (HA) nanoparticles via a co-precipitation method. Physico-chemical characterization was performed before and after calcination by Fourier transform infrared (FTIR) spectroscopy, solid state (31)P nuclear magnetic resonance (NMR) spectroscopy, and thermogravimetric analysis (TGA). The formation of nanocomposites was observed by wide angle X-ray diffraction (WAXD), scanning electron microscopy (SEM) with energy dispersive X-ray analysis (EDX), and transmission electron microscopy (TEM). The spectral and crystallographic data indicated the formation of hydroxyapatite in the presence of CMC. They were observed as aggregates of HA nanoparticles and CMC, whose sizes were approximately similar to 260 +/- 40 nm. The crystallite size of the hydroxyapatite particles decreased (with 2 wt% 18 +/- 3 nm) with increasing CMC content. The morphological aspects of the calcined samples revealed the sintering ability of HA nanoparticles. Nanocomposites of hydroxyapatite nanoparticles that mimic the process of nucleation and growth in nature can be prepared using biomacromolecules such as CMC.
Keywords: biopolymer; cellulose; hydroxyapatite; Nanoparticles; Particle size; X-ray diffraction

Silk fibroin and ceramic scaffolds: comparative in vitro studies for bone regeneration - Deshpande, Rucha; Shukla, Swati; Sayyad, Raeesa; Salunke, Shalmali; Nisal, Anuya; Venugopalan, Premnath (Bioengineering & Translational Medicine, 2021)
Synthetic bone void fillers based on calcium ceramics are used to fill cavities in the bone and promote bone regeneration. More recently, silk fibroin (SF), a protein polymer obtained from Bombyx mori silkworm, has emerged as a promising material in bone void filling. In this work, we have compared the safety and efficacy of two types of silk fibroin-based bone void fillers with currently used and commercially available ceramic bone void fillers (based on calcium sulphate, beta tricalcium phosphate, and beta tricalcium phosphate with hydroxyapatite). Further, we have also evaluated these two types of SF scaffolds, which have strikingly different structural attributes. The biocompatibility of these scaffolds was comparable as assessed by cytotoxicity assay, cellular adhesion assay, and immunogenic assay. Ability of the scaffolds to support differentiation of human mesenchymal stem cells (hMSCs) into an osteoblastic lineage was also evaluated in an in vitro differentiation experiment using reverse transcriptase polymerase chain reaction analysis. These results revealed that cells cultured on SF scaffolds exhibit higher expression of early to late markers such as Runx2, BMPs, collagen, osterix, osteopontin, and osteocalcin as compared with ceramic-based scaffolds. This observation was further validated by studying the expression of alkaline phosphatase and calcium deposition. We also show that scaffolds made from same material of SF, but characterized by very different pore architectures, have diverse outcome in stem cell differentiation.
Keywords: beta tricalcium phosphate; bone regeneration; bone void filler; calcium sulphate; hMSCs; hydroxyapatite; osteoblasts; scaffold; Silk fibroin

Imine oxidation catalyzed by zinc hydroxyapatite: kinetic studies - Vishwakarma, Rakhi; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (ChemistrySelect, 2023)
The synthesis of N,N-diphenylformamide from N-benzylideneaniline and urea hydrogen peroxide is investigated using a zinc hydroxyapatite (ZnHAP) catalyst. It was found that the catalyst resulted in the highest activity of 91 % conversion and 40 % selectivity at 130 degrees C in 2 h. A kinetic model was validated by Langmuir-Hinshelwood-Hougen-Watson (LHHW) at different temperatures and the absence of mass transfer resistance was proved by the Weisz Prater criterion. Effect of different catalysts, catalyst loading, temperature, mole-ratio, and speed of stirring was studied. The as-synthesized catalyst is characterized by FTIR, BET nitrogen adsorption-desorption, TEM, EDX, TPD-NH3, XPS, ICP-MS and XRD. ZnHAP catalyst was found to be stable up to three recycles with no loss in activity.
Keywords: heterogeneous catalysis; hydroxyapatite; imines; Oxidation; Reaction kinetics